Growth of total factor productivity (TFP) in the Algerian food industry: an econometric approach - بعار , عبدالحميد; أيث بارة , هاني (khazzartech الاقتصاد الصناعي, 2023)
This article assesses the growth of TFP in the food industry over the period from 1984 to 2018. The estimation of an ECM model allowed a better understanding of the long-term relationship between added value on the one hand, and capital and labor on the other hand. According to empirical results, returns to scale are constant and allow the determination of TFP and especially its link with the productivity of capital and the productivity of labor. Indeed, the TFP over the study period is determined by the productivity of capital and it increases with an average annual rate of 5.77%. Labor productivity is increasing with an average annual rate of + 9.41% and its impact on TFP is not decisive. In addition, that of the capital determines its evolution with a positive but weak annual growth of + 2.90% on average. On the other hand, the rate of growth of the PTF is weak because of the massive investments committed and the important staff employed in this industry. Consequently, there is considerable potential for improving total productivity through the productivity of labor and that of capital.